Public health implications of bovine Cysticercosis from cattle slaughtered at Dilla municipal abattoir, Southern Ethiopia - Fikadu Tesfaye (Hawassa University, 2020)
A cross sectional study was conducted during November 2013 to June 2014 to estimate the prevalence of Cysticercosis from abattoir survey and Taeniasis within the society found in and around Dilla town. Active abattoir survey and questionnaire survey were performed to accomplish the study. Of the total of 400 inspected cattle carcasses, 17 had varying number of C. bovis giving an overall prevalence of 4.25% (17/400). The prevalence of Cysticercus bovis showed significant difference (p<0.05) between male and female cattle. However, there was no significant difference (p>0.05)in the prevalence of Cysticercus bovis among the different Origins, breed, body condition score and age. Anatomical distribution of the cyst showed that highest proportions of C. bovis cyst were observed in shoulder muscle and tongue (29.41%), followed by, masseter muscle (23.53%), heart (11.76%) and liver (5.88%). Of the total 69 interviewed respondents, 57.79% (40/69) had contracted T.saginata infection. The majority of the respondent had an experience of row meat consumption as a result of traditional and cultural practice. The findings of this study including prevalence of C. bovis and questionnaire survey of taeniasis prevalence indicated the importance of Cysticercosis and Taeniasis in public health aspects. Therefore, due attention should be given to the public awareness and strict routine meat inspection in order to safe guard the public health